Intergenerational wealth transmission and mobility in great britain: What components of wealth matter? - Paul Gregg; Ricky Kanabar (University of Essex, Institute for Social and Economic Research (ISER), 2022)
The rapid widening of intergenerational wealth inequalities has led to sharp differences in living standards in Great Britain. Understanding which components of wealth are driving such inequalities is important for improving wealth and social mobility. We show the change in the intergenerational persistence in wealth in Great Britain is due to inequality in offspring housing wealth and that offspring homeownership has become increasingly stratified by parental wealth even after controlling for individual's own characteristics. Our findings imply the intergenerational wealth elasticity in housing wealth is set to double in approximately one century and highlight the increasingly important role parental wealth has for determining whether offspring hold and the rate at which they accumulate particular types of wealth.
Keywords: D31; D63; I24; 330; Wealth; Housing; Inequality; intergenerational mobility; Great Britain